2018
DOI: 10.3153/jaefr18006
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Awareness of People About Jellyfish Along the Southwest Coasts of Turkey

Abstract: This study is about a questionnary developed to collect data related awareness of people about jellyfish and injury cases. The questionnary was distributed to 226 people in the touristic areas of the west and the southwest regions of Turkey, with the participants consisting of holiday-makers, people working in the tourism sector, fishermen, divers as well as local dwellers. Overall, 78% of the participants had previous awareness of the existence of jellyfish, whereas the remaining 22% had heard about jellyfish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Penilia avirostris were found in very high numbers in these regions, often exceeding 2000 ind m -3 . Swarms of this species can be seen in the surface coastal waters and in shallow locations during the summer (Christou and Stergiou 1998, Gülşahin and Tarkan 2012, Killi and Sağdıç 2018. Some authors have suggested that temperature may play an important role in the population dynamics of P. avirostris (Atienza et al 2007, Gieskes 1971, Onbé and Ikeda 1995.…”
Section: Discussionmentioning
confidence: 98%
“…Penilia avirostris were found in very high numbers in these regions, often exceeding 2000 ind m -3 . Swarms of this species can be seen in the surface coastal waters and in shallow locations during the summer (Christou and Stergiou 1998, Gülşahin and Tarkan 2012, Killi and Sağdıç 2018. Some authors have suggested that temperature may play an important role in the population dynamics of P. avirostris (Atienza et al 2007, Gieskes 1971, Onbé and Ikeda 1995.…”
Section: Discussionmentioning
confidence: 98%